Analisis pengaruh kualitas layanan akademik terhadap kepuasan mahasiswa - Eka Ridha Nofrida; Khotim Hanifudin Najib (UMSU, 2023)
Student satisfaction is an important factor in maintaining and improving the quality of education. One factor closely related to student satisfaction is academic services. Universities can provide better services and enhance the level of student satisfaction. This study aims to analyze the influence of academic service quality on the satisfaction of students majoring in Elementary School Teacher Education. The research method used in this study is a survey method, utilizing a questionnaire as a data collection instrument. The variables of academic services are developed from the SERVQUAL theory, consisting of five dimensions: reliability, responsiveness, assurance, empathy, and tangibles, while student satisfaction is measured through five aspects: no complaints, recommended to others, confidence in expectations being met, tendency to say positive things, and not feeling hindered in obtaining the same. The research respondents are students enrolled in the Elementary School Teacher Education program from 2020 to 2022, totaling 359 students. The data analysis techniques include descriptive analysis and Spearman's rank correlation test. The results of the study indicate that all dimensions of academic services, including reliability, responsiveness, assurance, empathy, and tangibles, have an impact on student satisfaction.